Nerds, goths, geeks, and freaks : outsiders in Chicanx and Latinx young adult literature - Boffone, Trevor; Herrera, Cristina, 1978-; McCall, Guadalupe Garcia (Children's Literature Association series., 2020)
A much-needed intervention into the critical study of Chicanx and Latinx young adult literature.